Novel CARMIL2 Mutations in Patients with Variable Clinical Dermatitis, Infections, and Combined Immunodeficiency - Alazami, Anas M.; Al-Helale, Maryam; Alhissi, Safa; Al-Saud, Bandar; Alajlan, Huda; Monies, Dorota; Shah, Zeeshan; Abouelhoda, Mohamed; Arnaout, Rand; Al-Dhekri, Hasan; Al-Numair, Nouf S.; Ghebeh, Hazem; et al. (Frontiers in Immunology, 2018)
Combined immunodeficiencies are a heterogeneous collection of primary immune disorders that exhibit defects in T cell development or function, along with impaired B cell activity even in light of normal B cell maturation. CARMIL2 (RLTPR) is a protein involved in cytoskeletal organization and cell migration which also plays a role in CD28 co-signaling of T cells. Mutations in this protein have recently been reported to cause a novel primary immunodeficiency disorder with variable phenotypic presentations. Here we describe seven patients from three unrelated, consanguineous multiplex families that presented with dermatitis, eosophagitis and recurrent skin and chest infections with evidence of combined immunodeficiency. Through the use of whole exome sequencing and autozygome-guided analysis we uncovered two mutations not previously reported (p.R50T and p.L846Sfs) in CARMIL2. Real-time PCR analysis revealed that the biallelic frameshift mutation is under negative selection, likely due to nonsense-mediated RNA decay and leading to loss of detectable protein upon immunoblotting. Protein loss was also observed for the missense mutation, and 3D modeling suggested a disturbance in structural stability due to an increase in the electrostatic energy for the affected amino acid and surrounding residues. Immunophenotyping revealed that patient Treg counts were significantly depressed, and that CD4+ T cells were heavily skewed towards the naïve status. CD3/CD28 signaling impairment was evidenced by reduced proliferative response to stimulation. This work broadens the allelic heterogeneity associated with CARMIL2, and highlights a deleterious missense alteration located outside the leucine-rich region of the protein, where all other missense mutations have been reported to date.